Coronavirus Disease (COVID-19) and the risk of Post-Traumatic Stress Disorder: A mental health concern in Nepal - Asim, Mohammad; van Teijlingen, Edwin; Sathian, Brijesh (Nepal Journal of Epidemiology, 2020)
The sudden outbreak of Coronavirus-19 disease (COVID-19) is transforming the psychology and interpersonal relationships of millions across the globe. In Nepal, there is a need for national mental health surveys post COVID-19. This pandemic can cause traumatic experiences to the patients, caregivers, those quarantined and frontline healthcare providers which may lead to PTSD. Special attention should be focused on high-risk individuals, including policies to implement regular screening of PTSD symptoms.